2018
DOI: 10.1038/s41419-018-0292-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic fatty liver disease severity is modulated by transglutaminase type 2

Abstract: Non-alcoholic fatty liver disease (NAFLD) is one of the most important liver diseases worldwide. Currently, no effective treatment is available, and NAFLD pathogenesis is incompletely understood. Transglutaminase type 2 (TG2) is a ubiquitous enzyme whose dysregulation is implicated in the pathogenesis of various human diseases. Here we examined the impact of TG2 on NAFLD progression using the high-fat-diet-induced model in both wild-type and TG2-deficient mice. Animals were fed with a standard chow diet or a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…In addition, accumulating evidences show that autophagy is critical in metabolic homeostasis maintenance, protein quality control and mitochondrial network remodeling, which offers autophagy as an emerging target for treating cardiorenal metabolic disease 4 . Here, as PHB2 is an inner mitochondrial membrane mitophagy receptor 14 and autophagy is reported to be involved in disturbed lipid metabolism [44][45][46] , the roles of PHB2 on cardiac autophagy in heart failure or other cardiac pathologies should be further investigated in future studies.…”
Section: Phb2 Is a Potential Inner Mitochondrial Membrane Fao Regulatormentioning
confidence: 99%
“…In addition, accumulating evidences show that autophagy is critical in metabolic homeostasis maintenance, protein quality control and mitochondrial network remodeling, which offers autophagy as an emerging target for treating cardiorenal metabolic disease 4 . Here, as PHB2 is an inner mitochondrial membrane mitophagy receptor 14 and autophagy is reported to be involved in disturbed lipid metabolism [44][45][46] , the roles of PHB2 on cardiac autophagy in heart failure or other cardiac pathologies should be further investigated in future studies.…”
Section: Phb2 Is a Potential Inner Mitochondrial Membrane Fao Regulatormentioning
confidence: 99%
“…The observed structural changes indicate increased fission of mitochondria, and upregulation of fission proteins in the livers of HF diet-fed animals has been observed in several studies [159,218,220,221]. Ultrastructural electron microscopy (EM) analysis also revealed increased mitochondrial fission in the livers of HF diet-fed animals [220]. A blockade of mitochondrial fission by inducible ablation of DRP1 led to a massive reduction in HF diet-induced steatosis, liver damage and oxidative stress [221].…”
Section: Influence Of Nafld-inducing Diets On Liver Mitochondrial Mormentioning
confidence: 68%
“…Interestingly, one study showed the complete absence of mitochondrial changes under a HF diet when animals were forced to undergo regular endurance training [219]. The observed structural changes indicate increased fission of mitochondria, and upregulation of fission proteins in the livers of HF diet-fed animals has been observed in several studies [159,218,220,221]. Ultrastructural electron microscopy (EM) analysis also revealed increased mitochondrial fission in the livers of HF diet-fed animals [220].…”
Section: Influence Of Nafld-inducing Diets On Liver Mitochondrial Mormentioning
confidence: 90%
“…5). Opposing roles of TG2 in the onset of liver injury have been reported due to its dual function in the regulation of cell survival and death (15,29,30). Extracellular and cytoplasmic TG2 in the closed form exhibit multiple functions, such as GTPase, cell adhesion and scaffold activities, which are associated with cell growth and may prevent liver injury by favoring tissue stability (31).…”
Section: Resultsmentioning
confidence: 99%